Global dust storm signal in the meteorological excitation of Mars' rotation. Issue 5 (16th May 2013) - Zhou, Y. H.; Salstein, D. A.; Xu, X. Q.; Liao, X. H.
Abstract: [1] The meteorological excitation of Mars' rotation refers to the change of Mars' orientation parameters caused by meteorological processes, e.g., that portion due to variations of atmospheric circulation and surface pressure, and a cryospheric part due to the variable Martian polar ice caps associated with the CO2 sublimation/condensation effects. Global dust storms (GDSs) are unique meteorological events on Mars that cause changes in surface pressure, polar caps extent, and circulation patterns on a global scale, which in turn alter Mars' rotation under the conservation of Mars' total angular momentum. In this paper, the GDS signal in the meteorological excitation of Mars' rotation is investigated on seasonal, diurnal, and semidiurnal time scales, based on the Martian Climate Database. On seasonal scales, the cryospheric excitation plays a less important role in general, due to its location at high latitudes, than its atmospheric counterpart. The GDS brings (−3%, +15%) changes in the amplitude of annual polar motion and length‐of‐day (LOD) variation and (+22%, −34%) changes in the amplitude of semiannual polar motion and LOD variation. On diurnal and semidiurnal scales, the cryospheric excitation can be fully neglected in comparison to its atmospheric counterpart. A significant GDS signal is found with respect to the diurnal polar motion and semidiurnal LOD excitation variation, because of strong atmospheric tides arising from GDS effects. The amplitude increases in diurnal polar motion and semidiurnal LOD variation during some periods of the Martian year may reach 3–5 times as large as those during the same stage in a typical Martian year. Key Points: Global dust storm signal on Mars' diurnal/semidiurnal rotation is found Global dust storm exerts significant influences on Mars' seasonal rotation Cryospheric excitation is negligible on diurnal/semidiurnal scales